Gold-catalysed intramolecular reaction of alkynes with sulfoximines acting as N- and O-transfer reagents - Mackenroth, Alexandra; Antoni, Patrick W.; Shiri, Farshad; Bendel, Christoph; Mayer, Christian; Gross, Jürgen H.; Rominger, Frank; Rudolph, Matthias; Ariafard, Alireza; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2025)
Among the nucleophilic oxidants employed in the gold-catalysed oxidation of alkynes, sulphur-based reagents have played a substantial role since the beginning, granting access to the respective gold carbene intermediates. Herein, we describe the first example of the substance class of sulfoximines being used as atom transfer reagents to alkynes in gold catalysis. Based on the transformation of N-(2-alkynylphenyl) sulfoximines to 3H-indol-3-ones, it is demonstrated that the sulfoximine functionality is capable of selectively transferring first its nitrogen moiety to the alkyne, forming the α-imino gold carbene, which is then oxidised by the released sulfoxide moiety in a second step via a pseudo-intramolecular mechanism—a distinctive feature that differentiates this work mechanistically from earlier studies. A combination of extensive experimental and theoretical studies provides evidence for this mechanistic rationale. As no external reagents for the 1,2-difunctionalisation of the alkyne unit are required, a wide variety of functional groups are tolerated in the transformation, affording the desired 3H-indol-3-ones in mostly good yields. It was further also showcased that it is possible to combine our methodology with additional transformations of the 3H-indol-3-one core in one-pot procedures, allowing facile access to C2-quaternary indolin-3-one structures.
Gesehen am 18.06.2025